Interpreta y representa relaciones entre datos numéricos en grafico de barras en cuadricula - Pizarro Reina, Saira (2016)
The objective is to obtain the Bachelor's Degree in Primary Education with the application of the model class called: We represent and interpret bar graphs in grids, in the area of mathematics in the 40 students of the 2nd "A" of the Emblematic Educational Institution San Juan de la Libertad-Chachapoyas with a duration of 45 minutes on December 19, 2016, starting at 9: 00am. and ending at 9:45am. For its execution, the design of the implemented learning session that contains the general data, expected learning, evaluation, didactic sequence with the three moments of the session, pedagogical processes, strategies, means, materials and time was taken into account; with their respective theoretical support._x000D_ Concluding from the theoretical support_x000D_ The procedure that allows us to find the bar graph more easily is the manipulation of the concrete material relating it to some objects that have a grid shape._x000D_ A bar graph is a drawing that contains two lines; a vertical line in which the numbers are written and another horizontal line in which the names are written._x000D_ Bar charts are used to organize and compare data about people's tastes and preferences. In addition, they help us to identify through a quick reading which information has more or less preference._x000D_ The theoretical knowledge of the mathematical contents by the teacher facilitates the teaching and learning of the area._x000D_ All learning involves a relatively permanent change in behavior, thinking, and affect as a result of the experience._x000D_ The teacher acts in the class with clear purposes, creates the conditions for communication, teamwork, questions, doubts and clarifications, encouraging mistakes to be assumed as part of the learning process._x000D_ Concluding the pedagogical support_x000D_ To achieve better learning of mathematics, it is necessary to apply strategies that allow the student to work in an environment of peace and harmony, taking into account the approach of mathematics, problem solving._x000D_ A problem is a challenge, challenge or difficulty to solve for which a solution is not known in advance._x000D_ Mathematics didactic processes help students to solve different mathematical problems._x000D_ The evaluation is a process that seeks information for assessment and immediate decision-making, it focuses on a particular phenomenon, without trying to generalize to other situations.